Patterns of Outpatient Referral Cases before and after Implementation of National Health Coverage Program: Pola Kasus Rujukan Rawat Jalan sebelum dan sesudah Pelaksanaan Program Jaminan Kesehatan Nasional - Eka R. Gunardi; Arresta Suastika (Indonesian Journal of Obstetrics and Gynecology, 2020)
AbstractObjective: To understand the pattern of referral cases (accuracy of referral diagnosis, the accuracy of referral health facility and consistency of referral diagnosis) in obstetrics and gynaecology outpatient clinic before and after the implementation of JKN.Methods: This is an observational cross-sectional study using medical records of patients who were referred to obstetrics and gynaecology outpatient clinic in Dr. Cipto Mangunkusumo General Hospital in 2013 and 2014. Data were analyzed with bivariate analysis with chi-square, consisting of the accuracy of referral cases, accuracy of referral health facility, and consistency of referral cases before and after implementation of JKN.Results: There is a growing number of patients in obstetrics and gynaecology outpatient clinic after the implementation of JKN in 2014, which is 4.311 patients. Subjects were 222 cases, 104 cases from 2013 and 118 cases from 2014. From the analyzed data, the accuracy of referral diagnosis before JKN is 81.7% and after JKN 72.9%. (p=0.118), the accuracy of referral health facility before JKN is 63.5% and after JKN 71.2% (p=0.220), and the consistency of referral diagnosis before JKN is 89.4% and after JKN 84.7% (p=0.302).Conclusion: There is no statistically significant difference between the accuracy of referral diagnosis, the accuracy of referral health facility, and consistency of referral diagnosis before and after the implementation of JKN.Keywords: national health coverage program, obstetrics and gynaecology, outpatient clinic, referral AbstrakTujuan: Untuk memahami pola kasus rujukan (ketepatan diagnosis rujukan, ketepatan asal fasyankes perujuk, dan kesesuaian diagnosis rujukan) di Poliklinik Obstetri dan Ginekologi sebelum dan setelah pelaksanaan JKN.Metode: Penelitian ini adalah observasional potong lintang dengan menggunakan data rekam medis pasien yang dirujuk ke Poliklinik Obstetri dan Ginekologi RSUPN Dr. Cipto Mangunkusumo selama tahun 2013 dan 2014. Analisis dilakukan dengan analisis bivariat dengan chi square untuk membedakan ketepatan diagnosis rujukan, ketepatan asal fasyankes perujuk, dan kesesuaian diagnosis rujukan sebelum dan setelah pelaksanaan JKN.Hasil: Terdapat peningkatan jumlah kunjungan Poliklinik Obstetri dan Ginekologi sejak dilaksanakannya program JKN pada tahun 2014, yaitu sebanyak 4.311 pasien. Jumlah subjek adalah sebanyak 222 subjek, terdiri dari 104 subjek pada tahun 2013 dan 118 subjek pada tahun 2014. Dari analisis data, didapatkan tingkat ketepatan diagnosis sebelum JKN adalah 81,7% dan setelah JKN 72,9% (p=0,118), tingkat ketepatan fasyankes perujuk sebelum JKN adalah 63,5% dan setelah JKN 71,2% (p=0,220), serta tingkat kesesuaian diagnosis sebelum JKN adalah 89,4% dan setelah JKN 84,7% (p=0,302).Kesimpulan: Tidak ada perbedaan yang bermakna secara statistik antara ketepatan diagnosis rujukan, ketepatan fasyankes perujuk, dan kesesuaian diagnosis fasyankes rujukan sebelum dan sesudah pelaksanaan JKN.Kata kunci: jaminan kesehatan nasional, obstetri dan ginekologi, poliklinik, rujukan